Characterization of a midgut mucin-like glycoconjugate of Lutzomyia longipalpis with a potential role in Leishmania attachment - Myšková, Jitka; Dostálová, Anna; Pěničková, Lucie; Halada, Petr; Bates, Paul A; Volf, Petr (Parasites & vectors, 2016)
BACKGROUND: Leishmania parasites are transmitted by phlebotomine sand flies and a crucial step in their life-cycle is the binding to the sand fly midgut. Laboratory studies on sand fly competence to Leishmania parasites suggest that the sand flies fall into two groups: several species are termed "specific/restricted" vectors that support the development of one Leishmania species only, while the others belong to so-called "permissive" vectors susceptible to a wide range of Leishmania species. In a previous study we revealed a correlation between specificity vs permissivity of the vector and glycosylation of its midgut proteins. Lutzomyia longipalpis and other four permissive species tested possessed O-linked glycoproteins whereas none were detected in three specific vectors examined. RESULTS: We used a combination of biochemical, molecular and parasitological approaches to characterize biochemical and biological properties of O-linked glycoprotein of Lu. longipalpis. Lectin blotting and mass spectrometry revealed that this molecule with an apparent molecular weight about 45-50 kDa corresponds to a putative 19 kDa protein with unknown function detected in a midgut cDNA library of Lu. longipalpis. We produced a recombinant glycoprotein rLuloG with molecular weight around 45 kDa. Anti-rLuloG antibodies localize the native glycoprotein on epithelial midgut surface of Lu. longipalpis. Although we could not prove involvement of LuloG in Leishmania attachment by blocking the native protein with anti-rLuloG during sand fly infections, we demonstrated strong binding of rLuloG to whole surface of Leishmania promastigotes. CONCLUSIONS: We characterized a novel O-glycoprotein from sand fly Lutzomyia longipalpis. It has mucin-like properties and is localized on the luminal side of the midgut epithelium. Recombinant form of the protein binds to Leishmania parasites in vitro. We propose a role of this molecule in Leishmania attachment to sand fly midgut.
Keywords: Psychodidae; Digestive System; Insect Proteins; glykokonjugáty; Leishmania; Insect Vectors; hmyzí proteiny; Mucins; Lipophosphoglycan; Animals; muciny; Glycoconjugates; Phlebotomine sand flies; hmyz - vektory; Glycoprotein; zvířata; trávicí systém